Fluid flow and static structural analysis of E-glass versus S2-glass fiber/epoxy reinforced pipe joints - Bobba, Sujith; Leman, Z.; S., M. Sapuan; Zainudin, E. S. (International Commission of Agricultural and Biosystems Engineering, 2019)
Glass fiber/epoxy reinforced composite pipes are regularly used in the field were circulation of extreme pressured chemical fluids, transfer of industrial wastes, oil and natural gas transmission occurs. In oil and natural gas industry, the heavy crude oil transporting pipe lines are exposed to unsteady pressure waves which generate rise and fall stress levels in the pipes. Computational Fluid Dynamics Analysis was implemented using Ansys 15.0 Fluent software to investigate the consequences of these pressure waves on some detailed joints in the pipes. Relating on the type of heavy crude oil being employed, the flow behaviour stated a significant degree of stress levels in evident connecting joints, causing the joints to become weak over a sustained period of usage. In this analysis comparison of various pipe joints was done by using different material and the end result of the stress volume in the pipe joints were checked so that the life of the pipe joints can be optimized by the change of material.